Maternal and early onset neonatal bacterial sepsis: burden and strategies for prevention in sub-Saharan Africa. - Seale, A; Mwaniki, M; Newton, C; Berkley, J (2009)
Maternal and child health are high priorities for international development. Through a Review of published work, we show substantial gaps in current knowledge on incidence (cases per live births), aetiology, and risk factors for both maternal and early onset neonatal bacterial sepsis in sub-Saharan Africa. Although existing published data suggest that sepsis causes about 10% of all maternal deaths and 26% of neonatal deaths, these are likely to be considerable underestimates because of methodological limitations. Successful intervention strategies in resource-rich settings and early studies in sub-Saharan Africa suggest that the burden of maternal and early onset neonatal bacterial sepsis could be reduced through simple interventions, including antiseptic and antibiotic treatment. An effective way to expedite evidence to guide interventions and determine the incidence, aetiology, and risk factors for sepsis in sub-Saharan Africa would be through a multiarmed factorial intervention trial aimed at reducing both maternal and early onset neonatal bacterial sepsis in sub-Saharan Africa.